Transits of objects and people: traces of histories that connect the Africana Atlantic and Indian Ocean worlds - Neelima Jeychandran (22929070) (2025)
This article aims to expand the epistemological limits of the Indian Ocean by examining distinct examples that link the African and Indian worlds through objects, media and unconventional trajectories of exchange. While the histories of trade, migration and the circulation of objects between India and Africa, and along the western Indian Ocean rim, have been studied extensively, this article focuses on minor transnational circulations that compel us to reimagine African–Indian exchanges. In other words, I trace the transits of objects to emphasize non-linear mobilities, other networks, and rhizomatic imaginations of Africa and India that connect distant places and practices. First, I look at the arrival of African saints in western India during pre-modern times and their intertwined histories with precolonial empires and the Indian Ocean slave trade. Trade items and ritual objects associated with these saints connect them to terrains of exchange in the Misr (Egypt), Al-Habash (Ethiopia) and Nubia (Sudan and Nile Valley) regions, all important nodes that linked West Africa and the Indian Ocean through complex trans-Sahelian networks of traders, pilgrims and enslaved people. I then examine the circulation of trade goods, such as beads, textiles and umbrellas, that were produced in India for West African markets during the transatlantic slave trade, illustrating how colonial transcontinental networks used objects from the Indian Ocean to support their Atlantic enterprises through a complex system of commodity exchanges. The central objective is to demonstrate how lesser-known processes of circulation and transversal ontologies reveal the fraught and interconnected histories of the Africana Atlantic and Indian Ocean universe. Other Information Published in: Africa License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1017/s0001972025101216